Optimization of production logistics parameters in the digital economy - Fattakhov, Khamit (2018)
In this work problems of an efficiency evaluation of logistic providing the production organizations in the conditions of digital economy are considered. Authors predict "digitalization" of management systems by organizational structures, synergy consolidation of field of production management and logistics, combined use at the entities of approach of Lean and ERP systems. For effective logistic providing the entity in the conditions of digital economy it is offered to organize deliveries by the principles of E2E ("End-to-End"). Approach of E2E covers all supply chain, the principle of pulling to the supplier is implemented, the supplier completes and sends details under structure of the conveyor in a special container. The basic principles of E2E are: reducing warehouses and inventories, reducing frequency and usage time of transport, more effective work of the supplier, outsourcing of components, minimization of subassemblies, release of space for picking zones. In article the basic concepts and provisions of production logistics are specified, the balanced scorecard of an efficiency evaluation of logistic providing the entities in the conditions of digital economy was offered and formulas of calculation of cost efficiency of use of this principle in practical activities of the entity are developed.